Adequate flexibility potential to handle supply chain uncertainties - Immanuel Zitzmann; David Karl (The Road to a Digitalized Supply Chain Management: Smart and Digital Solutions for Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 25, 2018)
Risks and uncertainties (e.g. IT-system failure or demand fluctuation) threaten the performance of supply chains. This paper gives insight into the planning of flexibility potential as a crucial tool for managing the consequences of operational and disruptive uncertainties. A simulation study of lot-sizing decisions in a two-stage decentralised supply chain is used. The modelled supply chain faces operational as well as disruptive uncertainties. It is analysed how capacity and/or stock flexibility on each stage cope with unexpected events. The location of flexibility within the supply chain is key for its ability to handle uncertainties. The paper shows that stock flexibility can substitute capacity flexibility to a certain degree. However, disruptive uncertainties cannot be handled by stock flexibility alone. Therefore, trade-offs in flexibility potential have to be considered. In contrast to other studies, this simulation models operational and disruptive uncertainties in three areas: internal processes, supply side and demand side. Also flexibility management in a decentralised decision making process is analysed. Contrary to the lean thinking approach it is shown that inventory plays an important role in managing uncertainties. Therefore, management should use the right amount of inventory to create flexibility depending on the individual risk situation.
urn:nbn:de:gbv:830-88223277; 10419/209194; https://econpapers.repec.org/RePEc:zbw:hiclpr:25
Keywords: 650; Uncertaintiy; Supply Chain; Flexibility; Simulation Study